An investigation at the intersection of the sharing economy and supply chain management: a strategic perspective. Issue 11 (2nd November 2022) - Atkins, Ryan; Gianiodis, Peter
ABSTRACT: Research on the sharing economy (SE) frequently addresses consumer-facing logistics firms, but the broader supply chain remains under researched. In this study, we examine the effects of the SE on supply chain management (SCM) through a qualitative, internet-based exploratory study, employing an inductive categorisation process. By integrating theory from strategic management and organisational theory, this study proposes a framework of how incumbent firms can identify opportunities while neutralising possible threats of disruption emerging from the SE. Specifically, the framework predicts that by participating in the SE, incumbent firms gain efficiency in their transactions and the opportunity to refresh their relationship portfolios. Furthermore, participating in the SE allows these firms to develop ambidextrous capabilities. Thus, this study advances the SCM literature by providing a systematic analysis of the SE in the context of SCM, and by doing so, has laid a foundation for future research on this important topic.